Deep infiltrating endometriosis as a cause of severe urogynecological complications despite invasive treatment - report of two cases from the center of endometriosis surgery - D. Filipecka-Tyczka; A. Kajdy; B.P. Siekierski; M. Stańczyk; A. Rogowski; M. Rabijewski; R.B. Maksym (IMR Press, 2020)
Endometriosis involvement of the urological tract may lead to significant disabilities. The involvement of the urological tract gives rise to severe complications that burden patient health and quality of life. Two cases of patients with severe urogynecological complications after surgery of deep infiltrating endometriosis were analyzed. Last resort radical surgical treatment did not stop the progression of the disease and failed to prevent further deterioration despite concomitant hormone therapy. Careful clinical consideration is recommended to plan an effective therapeutic strategy and the extent of the surgery for this multidisciplinary and complex disease. The treatment should start and be proceed by a dedicated and experienced team. Radical surgery including a total hysterectomy with a salpingo-oophorectomy could be necessary. Although a radical dissection increases the chances of recovery and long-term remission, it is also associated with an increased risk of serious short-term and long-term postoperative complications. In presented cases, the infiltration of the ureter by endometriosis caused non-symptomatic kidney function loss. The radical surgical treatment of deep infiltrating endometriosis did not stop the progression of a disease and was associated with severe urogynecological complications. Screening for pyelocaliectasis in patients with deep endometriosis could be considered as an important part of preoperative examination and postoperative follow-up.